Using concept mapping to improve reading comprehension - Burtami Usman; Redha Mardatija; Siti Sarah Fitriani (Universitas Syiah Kuala, 2017)
This study was done to find out if reading comprehension ability of students from class X at SMAN 1 Sawang could improve significantly by using the Concept Mapping technique in teaching-learning reading EFL. True experimental design was employed in this study in which the sample 25% (30 students) was chosen by random sampling from the total population (118 students). The sample was divided into an experimental group (EG) and a control group (CG); each with 15 students. The EG was taught reading comprehension using the Concept Mapping technique, whereas the CG was taught using a conventional teacher centered approach. Tests were used as instruments to collect data which was analyzed using SPSS version 16. A questionnaire with a Likert scale was used to find out the students’ responses toward the use of Concept Mapping for learning reading comprehension. The t-test scores for the results from the pre-tests compared to those from the post-tests for both the EG and the CG were significant (p=0.006) which was lower than the degree of significance (0.05). The results indicated that the alternative hypothesis can be accepted and the null hypothesis rejected because the students of the EG achieved significantly better scores than those in the CG. Therefore, it can be concluded that using the Concept Mapping technique significantly improved the reading comprehension ability of students from class X at SMAN 1 Sawang.